Use of social media for the improvement of safety knowledge and awareness among Saudi Arabian phlebotomists - Attar, Razaz; Almohanna, Asmaa; Almusharraf, Ahlam; Alhazmi, Amal; Alanzi, Nouf; Al-Anezi, Fahad; Alanzi, Turki; Sroor, Raghad; Albishri, Ahmed; Alzahrani, Amwaj; Alsabilah, Taif; Alkenani, Ali; et al. (Frontiers in Medicine, 2023)
Purpose The purpose of this study is to investigate the use of social media for the improvement of safety knowledge and awareness among phlebotomists. Methods As this study was intended to arrive at specific conclusions using empirical evidence, a deductive quantitative cross-sectional online survey design was adopted. A total of 521 phlebotomists participated in the survey, and 86 incomplete responders were removed, resulting in a final sample of 435 considered in this study. T-tests and ANOVA were used to analyze the data. Results A total of 41.6% stated that social media was very effective, and 31.5% stated that it was somewhat effective in improving safety knowledge and awareness. in addition, this study revealed no major differences between male and female participants (p > 0.05) with respect to the effectiveness of social media. However, statistically significant differences (p < 0.05) among the age groups were identified in relation to the effectiveness of social media and the intention to use it in the future. Conclusion Social media applications are effective for knowledge dissemination among healthcare professionals.